Invasive diagnostic and therapeutic measures are unnecessary in patients with symptomatic van Neck–Odelberg disease (ischiopubic synchondrosis): a retrospective single-center study of 21 patients with median follow-up of 5 years. (4th May 2021) - Schneider, Kristian Nikolaus; Lampe, Lukas Peter; Gosheger, Georg; Theil, Christoph; Masthoff, Max; Rödl, Robert; Vogt, Björn; Andreou, Dimosthenis
Abstract : Background and purpose — Van Neck–Odelberg disease (VND) is a self-limiting skeletal phenomenon characterized by a symptomatic or asymptomatic uni- or bilateral overgrowth of the pre-pubescent ischiopubic synchondrosis. It is frequently misinterpreted as a neoplastic, traumatic, or infectious process, often resulting in excessive diagnostic and therapeutic measures. This study assessed the demographic, clinical, and radiographic features of the condition and analyzed diagnostic and therapeutic pathways in a large single-center cohort. Patients and methods — We retrospectively analyzed 21 consecutive patients (13 male) with a median age of 10 years (IQR 8–13) and a median follow-up of 5 years (IQR 42–94 months), who were diagnosed at our department between 1995 and 2019. Results — VND was unilateral in 17 cases and bilateral in 4 cases. Initial referral diagnoses included suspected primary bone tumor (n = 9), fracture (n = 3), osteomyelitis (n = 2), and metastasis (n = 1). The referral diagnosis was more likely to be VND in asymptomatic than symptomatic patients (4/6 vs. 2/15). More MRI scans were performed in unilateral than bilateral VND (median 2 vs. 0). All 15 symptomatic patients underwent nonoperative treatment and reported a resolution of symptoms and return to physical activity after a median time of 5 months (IQR 0–6). Interpretation — By understanding the physiological course of VND during skeletal maturation, unnecessary diagnostic and therapeutic measures can be avoided and uncertainty and anxiety amongst affected patients, their families, and treating physicians can be minimized.